Sosialisasi Pentingnya Peran Orang Tua dalam Perkembangan Literasi Anak di Desa Anjir Muara Kota Kecamatan Anjir Muara - Latifah, Latifah; Anza, Nadia El-Huda; Maidah, Rabiatul (Universitas Pahlawan Tuanku Tambusai, 2026)
Socialization is the means by which an individual acquires the knowledge, skills, and perspectives essential for functioning as an adult. Parents' role in the family is to help children learn many things and guide them with care and kindness. The ability to read and write is crucial, both now and in the future. Reading and writing are fundamental skills, like special tools within us, that help us solve problems and navigate new challenges as we grow. The methods used are lectures and question-and-answer methods. The purpose of this Community Service Program (PKM) is to ensure parents understand their role as individuals responsible for children's literacy development in Anjir Muara Kota Village. It is hoped that this PKM will foster a full sense of self-awareness in parents that they have an obligation to accompany, communicate, provide opportunities, supervise, motivate, and guide their children by providing stimulation or encouragement for their literacy development.